Efficient ternary bulk heterojunction solar cells based on small molecules only1. Issue 19 (21st May 2015) - Huang, Tzu-Yen; Patra, Dhananjaya; Hsiao, Yu-Sheng; Chang, Sheng Hsiung; Wu, Chun-Guey; Ho, Kuo-Chuan; Chu, Chih-Wei
<x xml:space="preserve">Abstract</x> Efficient ternary BHJ solar cells fabricated using small molecules—namely BDT6T, ICBA, and PC71BM—achieving a PCE of 6.36%.